ANALISIS KINERJA PEMBIAYAAN TAKE OVER PADA BTN SYARIAH DI TAHUN 2014- 2015 - JUWITA ANGGRAINI JUWITA; SITI MARDIYAH SITI (I-Finance Journal, 2016)
Since 2014, the growth of financing is slowed. This prompted the government to revise the policy Financing To Value and down payment financing of the property. Financing Take Over is one of the financing relating to the property. Therefore this study wanted to see is there any influence of this policy revision with the performance of the financing Take Over.The research methodology used is qualitative method with descriptive data analysis. This study analyzes the achievements that have been obtained on the financing of the take Over the BTN Syariah in 2014 until 2015. The results of the study found that the design contract used BTN Syariah is using Hiwalah and Murabahah contract, it is different from MUI No. 31 / DSN-MUI / VI / 2002, PBI Application no17 / 10 / PBI / 2015. The financing of Take Over had a significant impact both in quality and quantity of financing.Keyword : Take Over, Kinerja Pembiayaan, Financing To Value,